The uninvited corpse - Sennefelder, Debra (Sennefelder, Debra. Food blogger mystery series., 2018)
Leaving behind a failed career as a magazine editor and an embarrassing stint on a reality baking show, newly divorced lifestyle entrepreneur Hope Early thought things were finally on the upswing--until she comes face-to-face with a murderer... Hope's schedule is already jam packed with recipe testing and shameless plugs for her food blog as she rushes off to attend a spring garden tour in the charming town of Jefferson, Connecticut. Unfortunately, it isn't the perfectly arranged potted plants that grab her attention--it's the bloody body of reviled real estate agent Peaches McCoy... One of the tour guests committed murder, and all eyes are on Hope's older sister, Claire Dixon--who, at best, saw Peaches as a professional rival. And suspicions really heat up when another murder occurs the following night. Now, with two messy murders shaking Jefferson and all evidence pointing to Claire, Hope must set aside her burgeoning brand to prove her sister's innocence. But the closer she gets to the truth, the closer she gets to a killer intent on making sure her life goes permanently out of style...